ANALISIS DISIPLIN KERJA PEGAWAI NEGERI SIPIL DI UPTD LABOLATORIUM KESEHATAN (Studi Kasus Di Dinas Kesehatan Provinsi Nusa Tenggara Timur) - Tosi, Angel; Nursalam, Nursalam; Oktavianto, Aspri Budi (Journal Education and Government Wiyata, 2025)
The purpose of the study was to analyze the level of work discipline of civil servants at the UPTD Health Laboratory of East Nusa Tenggara Province. In analyzing the problem the author relates to the theory according to Muchdarsyah Sinungan 2003, because it focuses on indicators, namely, attendance, attitude and behavior and responsibility. The research method used is qualitative with a case study approach. The results of this study indicate that the level of employee discipline is still quite low, seen from employee attendance and timeliness. This study concludes that it is important to take more effective steps in increasing employee awareness and responsibility related to discipline, especially in terms of attendance and punctuality.